Emerging Technologies in The Audit Environment: Use and Perceived Importance Among Independent Auditors - Ali Alipourfallahpasand; Saideh Asgari (Iranian Journal of Accounting, Auditing & Finance)
To discover the possible weakness of knowledge and the use of a diverse group of technologies among independent auditors.The descriptive survey study was used to describe the level of usable importance of innovative technologies among 196 auditors and find any correlation between 31 emerging technologies and the audit firms' quality ranking.In general, this paper's results enumerate that Iranian auditors have a relatively acceptable knowledge and willingness to use emerging technologies, including Blockchain, Audit 4.0, etc. In auditing. However, due to various reasons such as lack of access to global markets, political and economic constraints, such facilitators are rarely used in auditing. For instance, technologies, including RPA, AI, and CPS, are not used by Iranian auditors. Although some items were deficient, the related tools' Importance level was moderate.This research suggests that due to businesses' failure to grow as much as innovative technologies, partners and decision-makers may believe that there is no need for emerging technologies in auditing. However, this may not be the case, as auditors generally emphasized that the importance level of technologies was moderate and high. There seems to be a positive correlation between audit firm's quality rankings and the use of emerging technologies in audit processes. There is no meaningful correlation between audit firms' quality rankings and the importance of emerging technologies.